(In)Visible signs of gender-based violence - Wagner, Anne; Condello, Angela (Gender, justice and legal feminism, 2025)
Unveiling the Paradox: Navigating the Visibility and Invisibility of Gender-Based Violence -- Part 1. Fluid Identities and Dynamics in Gender-Based Violence -- Leibnizian Response to Being Born this Way -- From Gender Binary ♀♂ to Gender Diversity ⚧ + X λ: Unveiling New Horizons in Societal Transformation -- On the Relation of Cause-Effect between Symbolic Violence and Gender-Based Violence -- Exploring Perspectives on Mass Violence: A Comparative Study of Banality of Evil Report and Feminist Theories on Conflict-Related Sexual Violence -- Catcalling as Demonstration of Masculinity in Public Space: Understanding Gender-Based Violence in Germany -- The Weak Subject: Talking about the Mediatic Representation of Gender-Based Violence -- Gender-Based Violence and some of its Forms in Modern Conditions -- The Terror of Hate – Conceptualizing Sexual Violence against Women as a Gender-Based Hate Crime -- Part 2. Empowering Voices, Combating Shadows: The Digital Frontier -- Gender-Based Violence: where are we at? Threats and Tools in the Digital Era -- Equal Access to Justice for Women: Is Legal Technology the Answer? Observations and Global Trends from Asia and Europe -- Gender-Based Violence in Cyberspace: An International Law Perspective -- Reforming AI for Gender Equality: An Examination of Canadian Algorithmic Impact Assessment -- Online Violence Against Women - A Contemporary Assessment of the Adequacy of the Online Safety Response -- A Platform for the Patriarchy: Offline Attitudes Driving Online Violence Against Women and Girls -- “A Nightclub Dancer also has a Master’s Degree?”: Features and Causes of Gender-Based Violence on Chinese Social Media Platform -- Gender Violence and Political Discourse in Colombia: An Analysis of the Use of Social Networks to Spread Hate -- Unveiling Technology-Facilitated Gender-Based Violence in South Korea - Signs of Gender-based Violence, Legal Reforms, and the Role of Criminal Law -- Part 3. Frameworks Intersected: Gender, Justice, and Societal Dynamics -- Disembodied Narratives and their Role in the Production of a Geography of Gender-Based Violence -- Iconizing, Gendering, and Ageing: the Semiotics of Italian Signer Mina between Face and Mask -- Invisible vs. Ordinary Child-based violence: To what Extent should the Corporal Punishment be evaluated? -- The Ambivalences of Labor Law for Gender Equality in Brazil and France -- Balancing Tradition and Gender Justice: Revisiting Section 9 of the Hindu Marriage Act and Its Impact on Women’s Autonomy and Constitutional Rights -- Making the Criminal Policy Discourse Visible: Obscurity of Sexual Consent in Spanish Regulations of Sex Crimes -- Afghanistan: Currency-Woman and the Global Moral Market -- (Un)Livable Minds: the Lived Experience of Trans and Gender-diverse people as Service Users of Mental Health Care Services in Barcelona.